Proteomics study on the effect of combined treatment of electrical pulses and tomato lipophilic extract in the downregulation of proliferating cell nuclear antigen in triple-negative breast cancer cell - Jeya Shree Thulasidas; Gowri Sree Varadarajan; Ignacio G. Camarillo; Uma K. Aryal; Lakshya Mittal; Raji Sundararajan (Elsevier, 2021)
Objective: To analyze the effect of electrical pulses (EP) with tomato lipophilic extract (TLE) on human, triple negative breast cancer (TNBC) cell (MDA-MB-231) and human epithelial, non-cancerous breast cell (MCF-10A) and to gain insights into the mechanisms of action. Methods: We prepared TLE using the solvent extraction method. We identified the constituents of TLE using LC-MS analysis. TLE with the dose of 250 μg/ml was combined with 800 V/cm, 100 μs, eight electrical pulses to treat cancerous MDA-MB-231 and non-cancerous MCF-10A breast cells, and their survivability was studied. We studied the proteins responsible for TLE's anticancer activity in TNBC cells using label-free, quantitative proteomics study. To understand the relationship between changes protein and transcription level, we did a real-time quantitative PCR (RT-qPCR) study. We detected Hydrogen Peroxide (H2O2) levels of both untreated and TLE/EP treated cells to determine how oxidative stress regulates various intracellular pathways. Results: TLE comprises fatty acids that heighten MDA-MB-231 cell proliferation. However, electrical pulses application nullifies these cell proliferative effects of fatty acids, as evident by the significant MDA-MB-231 cell viability reduction for TLE+EP treatment. Tomato extract, electrical pulses, and combinational treatment did not affect normal breast MCF-10A cells. A total of 1877 proteins were identified from the proteomics study. Conclusion: Applying EP in combination with TLE suppresses and reverses back the proliferative effects caused by TLE. EP and TLE+EP treatments increase hydrogen peroxide reactive oxygen species production in TNBC to inflict cell death due to excessive oxidative stress. Proteins, such as PCNA, LDHB, and ENO1, were downregulated in EP treatment, and it was confirmed with the mRNA levels by qPCR results. Our findings render innovative perceptions into the mechanisms of electrical pulses with TLE. Significance: Our research serves as a technological platform capable of identifying the set of proteins responsible for minimizing TNBC cell proliferation when treated with TLE+EP.